2023
DOI: 10.13167/2023.26.10
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Review on Hydrophobic Modification of Concrete: Progress and Perspectives

Abstract: The inherent nature of concrete is porous, hydrophilic, and microcracked, making it susceptible to water penetration into its matrix. This is the primary source of durability concerns. Furthermore, this type of penetration leads to considerable issues for concrete structures, resulting in significant financial burdens due to regular repairs and maintenance and a reduction in the structure's lifespan. In this study, the properties, uses, and advancements of hydrophobic concrete are investigated, focusing on dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
0
0
Order By: Relevance
“…For building concrete, the most commonly used hydrophobic modification methods are surface coating, hydrophobic treatment, and the addition of hydrophobic agents. [17] Sobolev and Batrakov [18] have shown that polyethylhydrosiloxanes and polymethylhydrosiloxane groups can form hydrophobic voids in concrete by releasing hydrogen. Wong et al [19] performed hydrophobic modification of cement mortar by PDMS, and the results showed that the concrete surface modified by PDMS was superhydrophobic, with a contact angle of 157.3° and a sliding angle of 8.7°.…”
Section: Introductionmentioning
confidence: 99%
“…For building concrete, the most commonly used hydrophobic modification methods are surface coating, hydrophobic treatment, and the addition of hydrophobic agents. [17] Sobolev and Batrakov [18] have shown that polyethylhydrosiloxanes and polymethylhydrosiloxane groups can form hydrophobic voids in concrete by releasing hydrogen. Wong et al [19] performed hydrophobic modification of cement mortar by PDMS, and the results showed that the concrete surface modified by PDMS was superhydrophobic, with a contact angle of 157.3° and a sliding angle of 8.7°.…”
Section: Introductionmentioning
confidence: 99%